Extended preservation of non-heart-beating donor livers with normothermic machine perfusion. - St Peter, S; Imber, C; Lopez, I; Hughes, D; Friend, P (2002)
BACKGROUND: Non-heart-beating donor (NHBD) livers represent an important organ pool, but are seldom utilized clinically and require rapid retrieval and implantation. Experimental work with oxygenated perfusion during preservation has shown promising results by recovering function in these livers. This study compared sanguinous perfusion with cold storage for extended preservation of the NHBD liver in a porcine model. METHODS: Porcine livers were subjected to 60 min of in vivo total warm ischaemia before flushing, after which they were preserved by one of two methods: group 1 (n = 4), University of Wisconsin (UW) solution by standard cold storage for 24 h; group 2 (n = 4), oxygenated autologous blood perfusion on an extracorporeal circuit for 24 h. All livers were subsequently tested on the circuit during a 24-h reperfusion phase. RESULTS: Livers in group 1 showed no evidence of viability during the reperfusion phase with no bile production or glucose utilization; they also displayed massive necrosis. Livers in group 2 demonstrated recovery of function by synthetic function, substrate utilization and perfusion haemodynamics; these livers displayed less cellular injury by hepatocellular enzymes. All differences in parameters between the two groups were statistically significant (P < 0.05). These findings were supported by histological examination. CONCLUSION: Warm ischaemia for 1 h and simple cold storage (UW solution) for 24 h renders the liver non-viable. Oxygenated, sanguinous perfusion as a method of preservation recovers liver function to a viable level after 24 h of preservation.